The 2015 EU‐Africa joint Valletta action plan on immigration: A parable of complex interdependence. (21st December 2021) - Tawat, Mahama; Lamptey, Eileen
Abstract: In 2015, as the "refugee crisis" unfolded, the European Union negotiated deals respectively with Turkey and many African countries to stem the influx of asylum seekers. But little comparatively has been said about its African deal, the Joint Valletta Action Plan (JVAP) and its impact. Using migration policy theories, this article shows that the African deal, embodied in the concept of "shared responsibility, " amounts to a special kind of interest, complex interdependence. Specifically, while parties held onto their interests (territorial integrity for the Europeans and economic development for the Africans), there was a new sense, especially on the part of the Europeans, that both parties needed each other's help (cooperation) to advance these interests. As a result, concrete measures such as the EU Emergency Trust Fund were formulated. Looking at their "effects, " these measures have been positive in most policy domains.